Rarity and endemism of flora in rock field (OCBIL) in the Serra do Espinhaço Biosphere Reserve (Revista Espinhaço, 2021)
Rare and endemic species are particularly important from the point of view of conservation, ecology and evolutionary biology. e aim of the study was to evaluate the rarity and endemism of species sampled in an area of rupestrian grassland. Data were collected in March 2019, ending in June of the same year. e method used in the sampling was the qualitative random walk. e Rabinowitz methodology was used to segregate species into rare or common, considering three variables: geographic distribution, habitat specificity and population size. Of the 100 species, 71% were rare and 29% were common. 78% of species were classified as endemic and 22% non-endemic. Of the species, 25% were exclusive to rupestrian fields and 75% occurred in other phytophysiognomies. is analysis contributed to the understanding of the rarity of species in the studied region and can contribute to conservation actions in Ocbil regions.
Keywords: Rupestrian Field; Conservation; Endemism; Rarity